(untitled) (Journal of Health Sciences, 2014)
Introduction: Clostridium difficile is the cause of the post antibiotic colitis. This anaerobe, sporogenous, gram-positive bacteria is most often recognized as the cause of the nosocomial diarrhea. The aim of this work is to show the impact of the infection Clostridium difficile on the result of rehabilitation of the patients that have been treated in the rehabilitation facility.Methods: 448 patients treated at the Clinic for physical medicine and rehabilitation of the Clinical Center University of Sarajevo were included in the study. Gender, age, Barthel index, length of hospitalization, and values of the albumin in the serum were documented. Kolmogorov-Smirnov test, Mann-Whitney U test and One Sample Wilcoxon Signed Rank test were used for data analysis.Results: There were 57% female and 43% of male patients. The average age was 67.5 years for women and 52 years for men. Barthel index at admission was 4.0 and at discharge raised to 8.0 (p=0.047). The length of the hospitalization for patients without infection was shorter (28.8 days) compared to patients with infection (43 days) (p=0.015). Values of the albumin in the blood at patients with confirmed Clostridium difficile infection were significantly lower than referent values (p = 0.016).Conclusion: Patients with Clostridium difficile infection had longer period of the rehabilitation and the results were less favorable.